Подготовка инженеров-педагогов и особенности профессиональной ориентации будущих специалистов автомобильного профиля - Адабашев, Бекир Велишаевич; Асанова, Фатма (НТУ "ХПИ", 2013)
Рассмотрены аспекты профессиональной подготовки инженеров-педагогов автомобильного профиля и возможности профессиональной ориентации, а также научные подходы к проблеме информатизации образования, влияющие на качество обучения.

The aspects of professional preparation of engineers-teachers of motor-car type and possibility of professional orientation, and also scientific approaches, are considered to the problem of informatization of education influencing on quality teaching.
Preparation of engineers-teachers and features of professional orientation of future specialists of motor-car type
Keywords: образование высшее; подготовка специалистов; подготовка кадров; технологии информационные; информатизация; мотивация; trade education; information technologies; profession; orientation; informatization; motivation